Multimedia Web Profile Design as Information Media In Kitchen Phase 17 - Wilianto Wilianto (Jurnal Minfo Polgan, 2025)
This study was conducted at Kitchen Phase 17, a culinary business located in Deli Serdang Regency, North Sumatra Province. The aim of this research is to create a web profile for Kitchen Phase 17, incorporating multimedia elements such as a profile video, to improve the delivery of information. The research utilized the SDLC (Software Development Life Cycle) method, with data collection carried out through observation, interviews, and literature review. The design process of the multimedia web profile consisted of several stages: system planning, analysis, design, implementation, and maintenance. The goal is that this website will help Kitchen Phase 17 effectively present information about its profile, food and beverage menus, and allow visitors easy access to view the offerings. Furthermore, the website will resolve current challenges in promoting and communicating information, ultimately broadening the scope and efficiency of information dissemination.